Decreased Monocyte HLA-DR Expression in Patients After Non-Shockable out-of-Hospital Cardiac Arrest. Issue 1 (July 2016) - Venet, Fabienne; Cour, Martin; Demaret, Julie; Monneret, Guillaume; Argaud, Laurent
Abstract : ABSTRACT: Out-of-hospital cardiac arrest (OHCA) constitutes a major health care problem with the development in immediate survivors of a post-cardiac arrest syndrome including systemic inflammatory response as observed in sepsis. As a decreased monocyte HLA-DR expression (mHLA-DR) has been repeatedly described in septic patients in association with an increased risk of death and nosocomial infections, we tested whether this immune alteration could also be observed after OHCA. Fifty-five non-shockable OHCA patients sampled at Day 0 (D0: within 4 h after OHCA), D1 (the next day), and D3: (after 2 additional days) were included. CD4+ lymphocyte count and mHLA-DR were evaluated by flow cytometry. We observed a marked decrease in mHLA-DR as early as D0 in patients compared with normal values. This decrease persisted till D3 and was associated with a moderate decrease in the number of circulating CD4+ lymphocytes. No correlations were identified between mHLA-DR and usual prognostic markers after OHCA. However, overtime evolution in mHLA-DR values appeared different between survivors and non-survivors with a quasisystematic decrease between D1 and D3 in non-survivors versus an increased expression in survivors. In conclusion, this preliminary pilot study describes the occurrence of OHCA-induced immune alterations as illustrated by a decreased mHLA-DR and CD4+ lymphopenia. Furthermore, we show for the first time the differential overtime evolution in mHLA-DR between survivors and non-survivors without association with usual prognostic markers and multiple organ failure. These initial results should now be confirmed in a larger cohort of OHCA patients.